2017
DOI: 10.1002/jat.3485
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticles induced cytotoxicity, oxidative stress and DNA damage in lymphocytes

Abstract: Over the past few decades nanotechnology and material science has progressed extremely rapidly. Iron oxide nanoparticles (IONPs) owing to their unique magnetic properties have a great potential for their biomedical and bioengineering applications. However, there is an inevitable need to address the issue of safety and health effects of these nanoparticles. Hence, the present study was aimed to assess the cytotoxic effects of IONPs on rats' lymphocytes. Using different assays, we studied diverse parameters incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 79 publications
1
47
0
Order By: Relevance
“…This study illustrates that a significant increase in MDA and LDH and depletion in GSH and CAT levels was observed in the tissue homogenates at a high dose of NPs indicating free radical generation. The elevated levels of MDA indicate the formation of hydroxyl radicals which in turn is associated with lipid membrane of tissue that may have led to inactivation of the enzymes by cross linking with MDA, which might have caused an increase in accumulation of ROS that could contribute to the inhibition of metabolic process and the onset of lesions in vital organs . Our results illustrated a dose dependent depletion of GSH, possibly due to enhanced utilization in both enzymatic and nonenzymatic reactions.…”
Section: Discussionmentioning
confidence: 62%
“…This study illustrates that a significant increase in MDA and LDH and depletion in GSH and CAT levels was observed in the tissue homogenates at a high dose of NPs indicating free radical generation. The elevated levels of MDA indicate the formation of hydroxyl radicals which in turn is associated with lipid membrane of tissue that may have led to inactivation of the enzymes by cross linking with MDA, which might have caused an increase in accumulation of ROS that could contribute to the inhibition of metabolic process and the onset of lesions in vital organs . Our results illustrated a dose dependent depletion of GSH, possibly due to enhanced utilization in both enzymatic and nonenzymatic reactions.…”
Section: Discussionmentioning
confidence: 62%
“…We have dealt with the application of USPIONs, and we investigated their effects on various organs of the WKY rats. As bare iron oxide nanoparticles administered in higher doses were previously shown to be toxic as they produce the development of oxidative stress [ 9 , 11 ], we used a low dose of PEG-coated magnetite USPIONs. PEG is a neutral, hydrophilic and biocompatible polymer which improves the dispersion of NPs in water, it improves their bio-distribution and increases blood circulation time [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a correlation between exposure to iron oxide NPs and metabolism is of particular concern in nanotoxicology related fields, as NPs can potentially enter to iron metabolism and, thus, to affect its physiological roles. Iron NPs may also increase reactive oxygen species production and to produce oxidative stress, which can further induce adverse effects on DNA, proteins as well as membrane lipids [ 9 , 11 ] and to induce inflammation, changes in blood pressure (BP) regulatory systems via modulation of vascular function. Yet, there is still limited information on the uptake of the USPIONs to the individual organs and tissues and their possible effects on metabolism and physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms underlying iron regulation in polarized macrophages remain unclear. Some studies14, 15, 16, 17 have shown that iron can induce high levels of ROS and DNA damage. Alternatively, ROS may also induce p53 due to DNA damage 3…”
Section: Introductionmentioning
confidence: 99%